2012
DOI: 10.1063/1.4748143
|View full text |Cite
|
Sign up to set email alerts
|

A link between nonlinear self-organization and dissipation in drift-wave turbulence

Abstract: Structure formation and self-organization in two-dimensional drift-wave turbulence show up in many different faces. Fluctuation data from a magnetized plasma are analyzed and three mechanisms transferring kinetic energy to large-scale structures are identified. Beside the common vortex merger, clustering of vortices constituting a large-scale strain field and vortex thinning, where due to the interactions of vortices of different scales larger vortices are amplified by the smaller ones, are observed. The vorte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…90 Studies of edge turbulence with GPI have shown nonlinear turbulent kinetic energy transfer from the background drift-wave turbulence into sheared quasi-static flows. 143 As suggested by earlier work 144,145 these results found that this energy transfer rate equals the local driftwave growth rate just before the L-H transition. The work on C-Mod showed for the first time that the large H-mode edge profile gradients develop after the transient zonal flow generation and turbulence suppression phenomena-clearly demonstrating the temporal sequence of events that leads to the H-mode regime.…”
Section: Edge Transport Barrier Physicssupporting
confidence: 63%
“…90 Studies of edge turbulence with GPI have shown nonlinear turbulent kinetic energy transfer from the background drift-wave turbulence into sheared quasi-static flows. 143 As suggested by earlier work 144,145 these results found that this energy transfer rate equals the local driftwave growth rate just before the L-H transition. The work on C-Mod showed for the first time that the large H-mode edge profile gradients develop after the transient zonal flow generation and turbulence suppression phenomena-clearly demonstrating the temporal sequence of events that leads to the H-mode regime.…”
Section: Edge Transport Barrier Physicssupporting
confidence: 63%
“…This structure depicts the streamline configuration of a vortex merger [41]. Around the two local maxima an equipotential line has developed, called the exchange band [41]. Via the exchange band particles and energy can be transferred from one vortex to the other.…”
Section: Gemr Simulationmentioning
confidence: 99%
“…3, the potential structures have united to one single structure, which is extended across the shear layer. This structure depicts the streamline configuration of a vortex merger [41]. Around the two local maxima an equipotential line has developed, called the exchange band [41].…”
Section: Gemr Simulationmentioning
confidence: 99%
“…In the case of drift wave turbulence, the power is transferred to low frequencies and low wavenumbers [47][48][49][50], leading to the power spectrum being skewed to low wavenumbers and low frequencies. This is called the inverse energy cascade [51].…”
Section: Strong Turbulence Regime δω?ω Lmentioning
confidence: 99%